Blink reflexes in severe traumatic coma. Issue 5 (May 1979) - Buonaguidi, R; Rossi, B; Sartucci, F; Ravelli, V
Abstract : Blink reflexes were studied in 21 patients in coma after severe head injury. Our observations suggest that blink reflexes are a simple, objective, neurophysiological test to evaluate brainstem function. Correlations between these reflexes and the anatomoclinical stanges of coma and the Glasgow coma scale have been established. Presence of the early R1 component shows the integrity of at least a part of the pontine structures. The appearance of the late R2 component is correlated with a better chance of recovery from coma.